Microwave-assisted co-gasification of mixed plastics and corn stover: A synergistic approach to produce clean hydrogen. (15th March 2023) - Abedin, Ashraf; Bai, Xinwei; Smith, Mark; Muley, Pranjali
Graphical abstract: Highlights: Microwave co-gasification of biomass and mixed plastics produced hydrogen-rich syngas. Synergy due to microwave heating was observed during co-gasification of plastics and biomass. Microwave triggers the decomposition of tar and light olefins. Microwave gasification resulted in high syngas yields, high hydrogen content of syngas and low tar yields compared to conventional gasification. Abstract: Co-gasification of waste plastic and corn stover into hydrogen is an effective way of reducing hydrogen cost and carbon footprint. However, current gasification technologies are energy intensive and cannot accommodate flexible feedstock. Microwave gasification offers several advantages including higher H2 yield and enhanced selectivity to syngas over tars. This work presents parametric optimization study of microwave co-gasification of mixed plastics and corn stover for hydrogen-rich syngas. High hydrogen yields of 30.5 mmolH2 /gfeed at 700 °C were obtained using a microwave reactor, as opposed to 0.9 mmolH2 /gfeed at 700–950 °C with conventional heating. Hydrogen yields are >98% of the theoretical extractable hydrogen from feedstock. Microwaves enhanced plastic and corn stover synergy and reduced tar yields. H-poor carbon formation resulting from the dehydrogenation of tar and coke, and light olefins decomposition, triggered by the external microwave electric fields, allowed further cracking of intermediate hydrocarbons to produce additional H2 .